Quality of life and cost consequence of delays in endovascular treatment for acute ischemic stroke in China - Weiyi Ni; Wolfgang Gerhard Kunz; Mayank Goyal; Lijin Chen; Yawen Jiang (Health Economics Review, 2022)
Background: Although endovascular therapy (EVT) improves clinical outcomes in patients with acute ischemic stroke, the time of EVT initiation significantly influences clinical outcomes and healthcare costs. This study evaluated the impact of EVT treatment delay on cost-effectiveness in China. Methods: A model combining a short-term decision tree and long-term Markov health state transition matrix was constructed. For each time window of symptom onset to EVT, the probability of receiving EVT or non-EVT treatment was varied, thereby varying clinical outcomes and healthcare costs. Clinical outcomes and cost data were derived from clinical trials and literature. Incremental cost-effectiveness ratio and incremental net monetary benefits were simulated. Deterministic and probabilistic sensitivity analyses were performed to assess the robustness of the model. The willingness-to-pay threshold per quality-adjusted life-year (QALY) was set to 71,000 (10,281). Results: EVT performed between 61 and 120 min after the stroke onset was most cost-effective comparing to other time windows to perform EVT among AIS patients in China, with an ICER of 16,409/QALY (2376) for performing EVT at 61-120 min versus the time window of 301-360 min. Each hour delay in EVT resulted in an average loss of 0.45 QALYs and 165.02 healthy days, with an average net monetary loss of 15,105 (2187). Conclusions: Earlier treatment of acute ischemic stroke patients with EVT in China increases lifetime QALYs and the economic value of care without any net increase in lifetime costs. Thus, healthcare policies should aim to improve efficiency of pre-hospital and in-hospital workflow processes to reduce the onset-to-puncture duration in China.
Keywords: 330; Cost-effectiveness; Acute ischemic stroke; Endovascular treatment